Global Commodities and the Indian Stock Market : A Post-Pandemic Volatility Spillover Analysis - G., Thouseef Ahamed; Tallapalli, Naresh Kumar; Akula, Pravallika; K., Shyam Kumar (Indian Journal of Finance, 2026)
Purpose : The paper analyzed the volatility spillovers between the global commodities (crude oil and gold) and the Indian stock market to find out whether the COVID-19 pandemic caused a structural break. It sought to determine whether the post-pandemic period was a new normal of risk transmission or a phase of returning to the long-run equilibrium. Design/Methodology/Approach : A multivariate GJR-GARCH dynamic conditional correlation (DCC) model was used to analyze the daily data from January 2016 to June 2025. A two-stage structural break analysis was used to achieve robustness: An independent samples t-test was applied to detect mean changes, and the Bai and Perron endogenous breakpoint test was used to differentiate between a permanent rupture and a transitory shock. Results : Although preliminary t-tests revealed that the post-pandemic correlation changes in the Nifty Energy and Auto index were significant compared to the pre-pandemic period, the Bai–Perron test showed that these changes were temporary stress rather than structural shifts. The aggregate market and the financial sector were resilient. Notably, the effectiveness of hedging was low (less than 2.5%), but the Auto sector experienced a certain decline in the protective power of Gold. Practical Implications : Investors need to be aware that although market structures might be resilient, protective hedges might fail in periods of stress. The conventional methods of diversification by Gold and Crude Oil require dynamic reconsideration, especially in energy-sensitive industries. Originality/Value : The current research has empirically distinguished between volatility stress and structural rupture at a sectoral level, which offers distinct evidence of resilience of the Indian market against non-financial global shocks.